Proactive tire maintenance - Danon, Gradimir (Journal of Applied Engineering Science, 2011)
Objective of the paper is to promote the proactive approach in tire maintenance for commercial vehicles and application of the Tire Pressure Monitoring System (TPMS). Researches have confirmed that the installation of TPMS on commercial vehicles is technically and economically justified, namely traffic safety and comfort of passengers would thus be significantly improved and operating costs would be decreased. Example of articulated city bus shows that the investment in the Tire Pressure Monitoring System would be recovered in the second year of operation.Key words: tire, pressure control, traffic accident, costs
Keywords: tires; costs; traffic accident; Pressure control